Evaluation of blood collection methods and anticoagulants for platelet function analyses on C57BL/6J laboratory mice. (16th November 2020) - Grill, Alexandra; Kiouptsi, Klytaimnistra; Karwot, Cornelia; Jurk, Kerstin; Reinhardt, Christoph
Abstract: The exploration of thrombotic mechanisms relies on the application of blood collection methods from laboratory mice with a minimal pre-activation of platelets and the clotting system. So far, very little is known on how the blood collection method and the anticoagulant used influence pre-activation of mouse platelets and coagulation. To determine the most suitable blood collection method, we systematically compared blood collection by heart puncture, Vena cava puncture, and puncture of the retro-orbital vein plexus and the use of citrate, heparin, and EDTA as frequently used anticoagulants with regard to platelet activation and whole blood clotting parameters. The activation of platelet-rich plasma diluted in Tyrode's buffer was analyzed by flow cytometry, analyzing the exposure of P-selectin and activated integrin αIIb β3 . Clotting of whole blood was profiled by thrombelastometry. Puncture of the retro-orbital vein plexus by plastic capillaries is not superior in terms of blood volume and platelet pre-activation, whereas heart puncture and Vena cava puncture resulted in similarly high blood volumes. Cardiac puncture and Vena cava puncture did not result in pre-activated platelets with citrate as an anticoagulant, but the use of EDTA resulted in increased levels of integrin αIIb β3 activation. Puncture of the retro-orbital vein plexus by plastic capillaries resulted in increased platelet integrin αIIb β3 activation, which could be prevented by soaking with citrate or coating with heparin. Further, activation of coagulation in citrated whole blood by puncture of the retro-orbital vein plexus using a blunt plastic capillary was observed by thromboelastometry. The use of citrate is the optimal anticoagulant in mouse platelet assays. Blood collections from the heart or Vena cava represent reliable alternatives to retro-orbital puncture of the vein plexus to avoid pre-activation of platelets and coagulation.